Electrocatalytic properties of spray-drying-synthesized cobalt or nickel phosphonate-derived materials. - Cabeza-Díaz, Aurelio; Vílchez-Cózar, Álvaro; Pérez-Colodrero, Rosario Mercedes; Bazaga-García, Montse; Cañamero-Cebrián, Fernando; Olivera-Pastor, Pascual (My University, 2023)
As a class of coordination polymers (CPs), metal phosphonates (MPs) are constructed by coordination bonds connecting metal sites and phosphonate (RPO32−) ligands, where the metal sites are dispersed uniformly at the atomic level. This feature facilitates the construction of OER/HER transition metal phosphide (TMP) pre-catalysts, making them very attractive precursors of Non-Precious Metal Electrocatalysts (NPMCs) [1, 2] In this work, we report the synthesis and crystal structures of several transition-metal phosphonates derived from the phosphonopropionic acid (PPA), [FexM1-x(HO3PCH2CH2COO)2(H2O)2; M=Co2+ or Ni2+; x= 0, 0.2]. These solids have been prepared for the first time by spray-drying synthesis directly on carbon paper (CP) (Scheme 1). Pyrolysis of spray-dried materials in 5%-H2/Ar led to TMP-based energy-conversion electrocatalysts. As compared with other conventional procedures, this synthetic methodology allowed to improve the water-splitting activity.
Keywords: Catálisis; Electrólisis; OER; HER; Electrocatalysts; Metal phosphonates; Water splitting